Pemberdayaan Guru Dan Orang Tua Paud: Pelatihan Pembuatan Kompos Sebagai Strategi Penguatan Literasi Lingkungan Dan Literasi Makanan - Titi Chandrawati; Susy Puspitasari; Gusti Nurdin; Adrian Rasyki; Rusanah Rusanah; Rahma Fatonah; Monika Handayani; Uliya Khoirun Nisa; Dian Novita (KENDURI : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
This Community Service Program (PKM) aims to empower early childhood education (PAUD) teachers and parents in Lengkong Kulon Village through participatory composting training. The program was motivated by the high volume of unmanaged household organic waste, limited community understanding of sustainable waste management, and the potential for integrating environmental and nutritional issues into early childhood learning. Conducted in November 2025, the program involved 15 participants (12 parents/guardians and 3 PAUD teachers). Implementation followed three phases: (1) preparation through coordination and module development, (2) implementation involving counseling, demonstration, and hands-on composting practice, and (3) evaluation through pre-test/post-test, observation, and post-training mentoring. Results demonstrated a significant increase in participants' knowledge, with mean scores rising from 52.3 (low category) to 85.7 (high category), with an average N-Gain of 0.70 (high category). All participants (100%) successfully practiced composting; 80% began sorting organic waste at home, and 60% used compost to fertilize household vegetable gardens. PAUD teachers initiated a "Our PAUD Garden" project and developed daily lesson plans integrating ecological values. The program contributes to community capacity building toward sustainability aligned with SDGs Goals 2, 4, 11, and 12. Practical-based training effectively builds ecological awareness and household food security